Clustering Countries on Attitudinal Dimensions: A Review and Synthesis - Ronen, Simcha; Shenkar, Oded (Academy of Management Review, 1985)
Eight empirical studies using attitudinal data to cluster countries are reviewed. The major dimensions accounting for similarities among countries are discussed, and a final synthesis of clusters is presented.